Forecasting U.S. Recessions and Economic Activity - Rachidi Kotchoni; Dalibor Stevanovic (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
This paper proposes a simple nonlinear framework to produce real-time multi-horizon forecasts of economic activity as well as conditional forecasts that depend on whether the horizon of interest belongs to a recessionary episode or not. Our forecasting models take the form of an autoregression that is augmented with either a probability of recession or an inverse Mills ratio. Our most parsimonious augmented autoregressive model delivers more accurate out-of-sample forecasts of GDP growth than the linear and nonlinear benchmark models considered, and this is particularly true during recessions. Our approach suits particularly well for the real-time prediction of final releases of economic series before they become available to policy makers. We use standard probit models to generate the Term Structure of recession probabilities at every period. Interestingly, the dynamic patterns of these Term Structures are informative about the business cycle turning points.
Keywords: 330